1996
DOI: 10.1097/00005650-199612000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Health as a Predictor of Physician and Patient Behavior in Medical Visits

Abstract: The patient's health status appears to influence physician-patient communication. In clinical practice, increased attention by physicians to their own and their patients' behavior may enhance diagnosis and prevent misunderstandings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(95 citation statements)
references
References 28 publications
7
86
1
1
Order By: Relevance
“…Hall et al [13] reported that the sicker or the more emotionally distressed patients were, the more complicated medical communication became. Among other things, they established that there was less social talk between doctors and sicker patients, that they tended to disagree with each other, exchanged more negative emotions, and that the relation was more ambiguous than with less sick patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hall et al [13] reported that the sicker or the more emotionally distressed patients were, the more complicated medical communication became. Among other things, they established that there was less social talk between doctors and sicker patients, that they tended to disagree with each other, exchanged more negative emotions, and that the relation was more ambiguous than with less sick patients.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate doctor-patient communication is considered of utmost importance in the process of guiding patients with complaints of fatigue, and it involves affective and instrumental behavior. When patients are sicker or emotionally more distressed, medical communication seems to be even more complicated [13]. In order to stimulate patients to disclose their concerns, it is necessary to establish adequate patient-centered communication [5,14].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, patient health may actually promote more humble behaviors in physicians: Physicians react more negatively to distressed patients than to healthy patients [20], so relatively healthy patients may enable physicians to behave more comfortably and securely, and thus more humbly, than they do with their less healthy patients during physician-patient interactions.…”
Section: Physician Humility Physician-patient Communication and Patimentioning
confidence: 99%
“…It is known for studies that patients' health status (physical as well as emotional) is associated with the length of the visit [29]. Not using the health status as a covariate may be confounding the results.…”
Section: Limitations Of the Studymentioning
confidence: 99%